Changes in soil aggregate‐associated enzyme activities and nutrients under long‐term chemical fertilizer applications in a phosphorus‐limited paddy soil. (28th December 2016) - Li, W. T.; Liu, M.; Jiang, C. Y.; Wu, M.; Chen, X. F.; Ma, X. Y.; Li, Z. P.
Abstract: Paddy soils in subtropical China are usually deficient in phosphorus (P) and require regular application of chemical fertilizers. This study evaluated the effects of chemical fertilizers on the distribution of soil organic carbon (SOC), total nitrogen (N) and available P, and on the activity of the associated enzymes in bulk soil and aggregates. Surface soils (0–20 cm) were collected from a 24‐yr‐old field experiment with five treatments: unfertilized control (CK), N only (N), N and potassium (NK), N and P (NP), and N, P and K (NPK). Undisturbed bulk soils were separated into >2, 1–2, 0.25–1, 0.053–0.25 and <0.053 mm aggregate classes using wet sieving. Results showed that both NP‐ and NPK‐treated soils significantly increased mean weight diameter of aggregates, SOC, available P in bulk soil and aggregates, as compared to CK. Most SOC and total N adhered to macro‐aggregates (>0.25 mm), which accounted for 64–81% of SOC and 54–82% of total N in bulk soil. The activities of invertase and acid phosphatase in the 1–2 mm fraction were the highest under NPK treatment. The highest activity of urease was observed in the <0.053 mm fraction under NP treatment. Soil organic carbon and available P were major contributors to variation of enzyme activities at the aggregate scale. In conclusion, application of NP or NPK fertilizers promoted the formation of soil aggregates, nutrient contents and activities of associated enzymes in P‐limited paddy soils, and thus enhanced soil quality.